Gear mesh stiffness of polymer-metal spur gear system using generalized Maxwell model. (September 2022) - Chakroun, Ala Eddin; Hammami, Chaima; Hammami, Ahmed; De-Juan, Ana; Chaari, Fakher; Fernandez, Alfonso; Viadero, Fernando; Haddar, Mohamed
Highlights: Using rheology in a polymer-metallic spur gear system. Simulating the viscoelastic behavior of nylon 6, 6 using generalized Maxwell model. Identifying parameters using parameter identification method Poel-zero formulation. Deducing gear mesh stiffness of polymer-metallic gear for different temperatures. Abstract: Polymer-metal gears become increasingly interesting to manufacturers and researchers for their advantages to combine the two material's efficiencies. Despite the variety of studies in the literature, there is a significant drop in the number of studies concerning the Gear Mesh Stiffness (GMS). The variation of the GMS by time has a major influence on the dynamic response of transmission. Therefore, this study proposes to take into consideration the viscoelastic behavior of polymer in order to model effectively the GMS of a gear system. The suggested rheological model is the Generalized Maxwell Model (GMM). It is first used to model the viscoelastic behavior of the plastic material of the pinion. Then, Pole Zero Formulation (PZF) is employed to identify parameters of the proposed model. A numerical simulation is then carried out to illustrate the results of this new approach adopted on a pure Nylon 6, 6-steel pinions. The evolution of the GMS is illustrated to highlight the viscoelastic behavior's model presented in this paper. Finally, the influence of the change in the temperature is investigated.